(untitled) (XXI Century. Spanish Literature and Culture, 2013)
The current poetry scene, elusive to any taxonomy, suggests a clear heterogeneity of lyrical proposals and perspectives. None of them can be used as a new one, but all must be conceived as a finisecular poetic legacy. This aesthetic heritage, emphasizes the permanence of the use of culturalist references of clear postmodern nature.